A 'benign' condition masquerading as arthritis. (5th August 2013) - V, Shanmugapriya; B, Subashini; K, Brindha; S, Shobhana
Abstract : A 9 year-old boy presented with a 3-week history of low-grade fever, on and off, and additive arthritis of the lower limb joints with no overt antecedent trauma. Investigations for juvenile idiopathic arthritis (JIA), reactive and tuberculous arthritis were normal. He was started on anti-inflammatory drugs as for seronegative oligoarticular JIA. Since arthritis persisted despite treatment, MRI of the left knee joint was planned prior to an aspiration/synovial biopsy. MRI revealed a partial tear of the anterior cruciate ligament with a significant effusion. On careful re-examination, at this point, he was found to have generalised hypermobility with a Beighton score of 9/9. This had been missed initially, leading to a delay in diagnosis and management. He was managed with careful physiotherapy and lifestyle modification. The left knee effusion resolved within a month. This case is being reported in order to highlight the fact that joint hypermobility syndrome can be misdiagnosed as arthritis.